Case report: NUDT15 polymorphism and severe azathioprine-induced myelosuppression in a young Chinese female with systematic lupus erythematosus: a case analysis and literature review - Gu, Juan; Lin, Yupei; Wang, Yuhe (Frontiers in Pharmacology, 2023)
Azathioprine is clinically used as an immunosuppressant for treating autoimmune diseases. However it has narrow therapeutic indices due to frequent myelosuppression. Polymorphic variants of genes coding for thiopurine S-methyltransferase (TPMT) and nucleoside diphosphate-linked moiety X motif 15 (NUDT15) are critical determinants of AZA intolerance, and the differences in frequencies of the two genetic variants exist among people of different ethnicities. Most reports regarding NUDT15 variant, AZA-induced myelosuppression occurred in patients with inflammatory bowel disease and acute lymphoblastic leukemia. Moreover, detailed clinical characteristics were not frequently reported. Here we present the case of a young Chinese female with the NUDT15 c.415C>T (rs116855232, TT) homozygous variant and wild-type TPMT*2 (rs1800462), TPMT*3B (rs1800460), and TPMT*3C (rs1142345) who received high doses of AZA (2.3 mg/kg/d) for systematic lupus erythematosus and had not been told to undergo routine blood cell counts during AZA ingestion. The patient had suffered from severe AZA-induced myelosuppression and alopecia. Moreover, dynamic changes in blood cell counts and responses to treatment were observed. We also conducted a systematic review of published case reports of patients exclusively with NUDT15 c.415C>T homozygous or heterozygous variants to review the characteristics of dynamic changes in blood cells so as to provide reference information for clinical treatment.